Corporate brand identity management in a technological faculty – how brand relationships influence students and companies reputations - Barros, Teresa (2013)
Identity is traditionally defined as an emission concept [1]. Yet, some research points out that there are external factors that can influence it [2]; [3]; [4]. This subject is even more relevant if one considers corporate brands. According to Aaker [5] the number, the power and the credibility of corporate associations are bigger in the case of corporate brands. Literature recognizes the influence of relationships between companies in identity management. Yet, given the increasingly important role of corporate brands, it is surprising that to date no attempt to evaluate that influence has been made in the management of corporate brand identity. Also Keller and Lehman [6] highlight relationships and costumer experience as two areas requiring more investigation. In line with this, the authors intend to develop an empirical research in order to evaluate the influence of relationships between brands in the identity of corporate brand from an internal perspective by interviewing internal stakeholders (brand managers and internal clients). This paper is organized by main contents: theoretical background, research methodology, data analysis and conclusions and finally cues to future investigation.